2021
DOI: 10.1159/000517816
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breast Reduction Surgery on Long-Term Breast Cancer Risk in Austria

Abstract: <b><i>Introduction:</i></b> Breast reduction surgery is one of the most frequently performed surgeries amongst plastic and reconstructive surgeons worldwide. Previous studies have shown decreased risk of breast cancer development in women undergoing breast reduction surgery of up to 28%. We aimed to evaluate the relative risk of breast cancer development in our patients after breast reduction surgery in relation to the general female population of Austria. <b><i>Methods:<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“… 3 Similarly, a recent population-based analysis of 637 women who underwent breast reduction surgery between 2003 and 2017 in Austria found that there was a reduction in breast cancer incidence of approximately 82% after breast reduction. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Similarly, a recent population-based analysis of 637 women who underwent breast reduction surgery between 2003 and 2017 in Austria found that there was a reduction in breast cancer incidence of approximately 82% after breast reduction. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 32 Similarly, a recent study by Niepel et al found a reduction in breast cancer incidence of 82% in women who underwent breast reduction surgery compared with the general population. 33 Breast reduction may serve as an acceptable alternative for many women who do not wish to pursue more aggressive measures, such as prophylactic mastectomy. The principle of removing additional breast tissue resulting in improved oncologic outcomes, specifically breast cancer risk reduction, seems to hold true for both patients who undergo breast reduction or those who receive OPS.…”
Section: Breast Reduction and Risk Reductionmentioning
confidence: 99%